Terminología erótica: análisis léxico contrastivo de Confession de mademoiselle Sapho ou Anandria de Pidansart de Mairobert y su traducción por López Barbadillo - Lence Guilabert, Ángeles (Anales de Filología Francesa, 2010)
Joaquín López Barbadillo, a spanish writer and journalist who died in 1922, translated into spanish the book by Pidansart de Mairobert which was originally published in 1784. The translator, while remaining quite faithful to the french text, introduces lexical differences which, at times, renders the terminology more obscene or moralistic, without changing the meaning of the original erotic work. Based on examples taken from both versions and subsequent to the creation of a repertoire of character names and places mentioned, this analysis concludes with a bilingual glossary of erotic terminology.